The political organization of Oman from the Second Imamate period to the Yaʻrūba: rereading Omani internal sources - Salimi, Abdulrahman al- (2013)

Early Ibāḍī Theological Arguments on Atoms and Accidents - Salimi, Abdulrahman al- (Arabic Sciences and Philosophy, 2013)
Le gros de la recherche orientaliste consacrée à la littérature théologique islamique a négligé les idées théologiques Ibāḍī à portée cosmologique, ce qui a conduit à une compréhension incomplète de la théologie islamique et à un manque considérable dans la recherche occidentale. L'omission de ce mouvement important de l'Islam est compréhensible étant donné que les textes Ibāḍī ne sont accessibles, publiés, diffusés et traduits que de façon très partielle. Cette étude vise donc à combler certaines de ces lacunes dans la recherche sur la première théologie islamique. Les objectifs de cet article sont de: 1) caractériser la littérature Ibāḍī classique portant sur la théorie atomiste de la substance et de l'accident; 2) examiner les textes d'auteurs Ibāḍī du iiie/ixe siècle dialoguant et discutant avec d'autres écoles théologiques islamiques, à savoir les Muʿtazilites pré-Bahshamiyya (Abū Hāshim al-Jubbāʾī, d. 321/933) et les Ashʿarites (Abū al-Ḥasan al-Ashʿarī, d. 324/936), en lien avec la théorie atomiste de la substance et de l'accident; 3) passer en revue le grand nombre d'opinions soutenues parmi les premiers théologiens Ibāḍī, et examiner les sources et les thèmes spécifiques susceptibles d'avoir influencé cette école de pensée diversifiée. Cet article cherche aussi à identifier des traits communs dans l'approche Ibāḍī durant la période de formation de la théologie islamique, et à explorer les voies grâce auxquelles ces premiers théologiens ont pu avoir accès à des thèmes cosmologiques antérieurs à l'Islam.

The Ibadis in the region of the Indian Ocean. Sect. 1: East Africa - Gaube, Heinz (Georg Olms Verlag, 2013)
Keywords: Ibadisme – Afrique de l'Est

Muslims, Scholars, Soldiers: The Origin and Elaboration of the Ibadi Imamate Traditions * By ADAM GAISER. - Salimi, Abdulrahman al- (Journal of Islamic Studies, 2013)
Keywords: Recension

The Essentials of Ibāḍī Islam, by Valerie J. Hoffman - Salimi, Abdulrahman al- (Ilahiyat studies, 2013)
Keywords: Recension

The South East European View - Ziaka, Angeliki (Oman and overseas, 2013)

Oman and Ibadism in Modern French Historiography: Assessing a Semi-Failure - Dridi, Moez (Oman and overseas, 2013)

The Formation of Oman’s Maritime Power under the Yaariba and Sayyid Said - Staples, Eric (Oman and overseas, 2013)

Oman: The Russian View since the 15th Century - Rezvan, Efim (Oman and overseas, 2013)
Keywords: Récits de voyage – Oman

Ibadis in East Africa: Archaeological and Historical Evidence - Horton, Mark (Oman and overseas, 2013)
Keywords: Archéologie – Zanzibar

Umani Ports in Chinese Sources - Kauz, Ralph (Oman and overseas, 2013)

A Political Culture and Foreign Policy Shaped by a Moderate Religious View: The Case of the Sultanate of Oman - Rabi, Uzi (Oman and overseas, 2013)
Keywords: Vie politique – Oman – 1970-2020

Mosaic Oman: Views from India - Dietl, Gulshan (Oman and overseas, 2013)

From Slumber to Assertion: Maritime Expansion of the Ibadis of Oman and the Responses of Estado da India,1622–1720 - Malekandathil, Pius (Oman and overseas, 2013)

Omani Seafaring and Omani Boat - Vosmer, Tom (Oman and overseas, 2013)
Keywords: Archéologie – Oman

The British Historical View of Oman and Ibadism - Worrall, James (Oman and overseas, 2013)

The Portuguese in East Africa and the Omani Reconquest of East Africa - Newitt, Malyn (Oman and overseas, 2013)
Keywords: Relations – Oman – Portugal

Oman through Jewish Travellers’ Eyes - Schreiner, Stefan (Oman and overseas, 2013)
Keywords: Judaïsme – Oman; Récits de voyage – Oman

The Seminar für Orientalische Sprachen (SOS) at Berlin: Aspects of the Relationship between Oman and Germany in the Late 19th and Early 20th Century - Hoffmann-Ruf, Michaela (Oman and overseas, 2013)
Keywords: Relations – Oman – Allemagne

Wood, Horses and Friendship. The Arabic Letters from Muscat to the Dutch in Kochi (1779) and Batavia (1798–1806) - Witkam, Jan Just (Oman and overseas, 2013)

Late pre-Islamic Oman: The Inner Evidence – The Outside View - Yule, Paul A. (Oman and overseas, 2013)
Keywords: Archéologie – Oman

The Main Languages of East Africa and their Literatures - Bakari, Mohammed Ali (Oman and overseas, 2013)
Keywords: Littérature – Zanzibar

A Historical Survey of US-Omani Relations from 1790 to the Present - Leonard, Douglas R. (Oman and overseas, 2013)
Keywords: Relations – Oman – Etats-Unis

Omani Trade and Cultural Relations with East Asian Countries - Ziaee, Ali Akbar (Oman and overseas, 2013)
Keywords: Commerce – Oman

African Perspectives - Kusimba, Chapurukha M. (Oman and overseas, 2013)

The Origins of Omani Identity - Wilkinson, John Craven (Oman and overseas, 2013)

The Growth of the Relationships between Oman, the Gulf and the Western Waters of the Indian Ocean. Oman: The Corner-Stone of a Maritime System - Piacentini Fiorani, Valeria (Oman and overseas, 2013)

Omani Seafaring Identity before the Early 1600s: Ethnic and Linguistic Diversity - Agius, Dionisius A. (Oman and overseas, 2013)
Keywords: Navigation – Oman

Danish and Norwegian Travel Accounts of Oman, 1765–1995: Changing Views across Sea and Land - Bang, Anne K. (Oman and overseas, 2013)
Keywords: Récits de voyage – Oman

Oman: The Arab Views - Ghazal, Amal N. (Oman and overseas, 2013)

Zanzibar: The Sultanate and the Ottoman State in Africa - Gol, Mohammed Z. (Oman and overseas, 2013)

The Swahili Coast: Africa’s Window on the Indian Ocean - Sheriff, Abdul Mohamed Hussein (Oman and overseas, 2013)

Historical Coincidences between Oman and Brazil: Portuguese Invaders, African Slaves and the Majlis al-Jinn - Pacheco, Leila M. S. (Oman and overseas, 2013)
Keywords: Esclavage – Oman

Oman and Omanis in Portuguese Sources in the Early Modern Period (ca. 1500-1750) - Cunha, João Teles e (Oman and overseas, 2013)
Keywords: Relations – Oman – Portugal